Perbandingan Efektivitas Cairan Pendingin pada Liquid Cooling System dengan Website Simscale untuk Mengurangi Biaya Produksi dan Operasional - Andrea Songklanaita; Anry Christiano Tambunan; Muhammad Rey Renoult; Fitra Rizki Aleva; Prasasti Alamsyah; Putra Ramanda; Uvi Desi Fatmawati (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
The rapid development of technology demands solutions to optimise heat management for electronic components. Through this study, the researchers evaluated the effectiveness of various types of coolants in a liquid cooling system for electrical equipment, especially CPUs. Using design simulations conducted through SolidWorks software, this research aims to optimise the flow rate and selection of coolant type to achieve maximum thermal efficiency and reduce production and operational costs. The simulation results show that water is the most efficient coolant with significant temperature reduction compared to Ethylene Glycol (EG), Propylene Glycol (PG), and silicone oil. Water shows a temperature drop of 11.76°C, while EG and PG show a temperature drop of 8.82°C and 7.35°C respectively and silicone oil shows a temperature drop of 4.9°C. It can be seen from the simulation that water shows the most effective temperature reduction compared to EG, PG, and Silicone Oil.